Analyzing the Impact of PGSD Students Interpersonal Intelligence on Mathematical Communication Skills of Students in Microteaching Sessions - Dewi Anjarsari; Rizka Latifah (Universitas Sebelas Maret, 2026)
Communication mathematical is competence crucial that allows student for convey and understand draft mathematics in a way effective, so that very important for success learning. Although thus, many student school bases Still experience difficulty in communicate idea mathematical in a way clear. Interpersonal intelligence of students prospective school teachers basic (PGSD) is believed own role important in push effective interaction during microteaching sessions, so that potential increase ability communication mathematical students. However, research that specifically direct study influence interpersonal intelligence of prospective teachers towards ability communication mathematical student Still limited, so that there is gap in literature. Research This aim for analyze influence interpersonal intelligence of PGSD students towards ability communication mathematical student school base in microteaching session. With use design study quantitative correlational, data collected through questionnaire interpersonal intelligence filled by PGSD students and tests communication given mathematics to students. Analysis regression used for test connection predictive between interpersonal intelligence and abilities communication mathematical students. Research results show existence influence positive and significant, which indicates that level students' interpersonal intelligence prospective teachers in contact close with improvement ability communication mathematical students. Findings This confirm importance integration development interpersonal intelligence in curriculum teacher education, in particular in microteaching practices, for optimize effectiveness teaching and results Study mathematics students. Research This give contribution important for educators and creators policy in effort increase quality education mathematics at school base through development competence prospective teacher.